Profile of aeroallergen sensitizations in allergic patients living in southern Vietnam - Trinh, Tu HK; Nguyen, Phuong TM; Tran, Tai T; Pawankar, Ruby; Pham, Duy L (Frontiers in Allergy, 2023)
Background Climatic and geographical characteristics may alter the plant distribution and thereby the patterns of allergens. Objective To evaluate the profile of allergen sensitization in patients in southern Vietnam and its association with allergic diseases. Methods We collected data of 423 patients who visited the Unit of Allergy and Clinical Immunology, University Medical Center, Vietnam from 2014 to 2021, from their medical records. Patients underwent skin prick tests to the 12 most common aeroallergens. Clinical evaluation and diagnosis of allergic diseases was done in consert with their allergen sensitization status. Results Mites and cockroach were the most prevalent sensitizing allergens, with the sensitization prevalences as followed: Dermatophagoides farinae (Df) (59.8%), Dermatophagoides pteronyssinus (Dp) (50.4%), Blomica tropicalis (Bt) (49.6%), storage mites mix (10.4%), and cockroach (10.2%). Sensitization to Df was more predominant in males than in females (66% vs 54.1%). Dp-sensitized patients were younger than non-sensitized patients (29.01 ± 13.60 vs. 32.17 ± 14.89) whereas storage mites-sensitized patients were older than the non-sensitized groups (36.25 ± 13.53 vs. 28.76 ± 13.39) (p < 0.05 for all). A considerable proportion of patients with urticaria, allergic rhinitis, and atopic dermatitis were sensitized to mites. Polysensitization to different species of house dust mites (Dp, Df) and storage mites (Bt) was prevalent among patients sensitized to any kind of mites. Conclusions Among people living in southern Vietnam, HDM mites, and cockroach were the predominant allergens. Further studies on the factors regulating the association between allergen sensitization with allergic diseases and polysensitization are crucial.